Klistir kot rutinski postopek pri porodu - Perko, Vanja (Obzornik zdravstvene nege, 2011)
Introduction: Pregnancy, birth and postpartum are physiological periods in which health care workers often intervene too much in the last decades. Some of the interventions are believed to be unnecessary, like shaving of the perineum, artificial ruptures of membranes, intravenous application of fluids and also routine enemas. Methods: The article presents a review of literature on the theory and practice of enema administration as a routine antenatal preparation process. Discussion and conclusions: Enema as a birth preparation procedure is still widely used in Slovenia. There is no evidence based justification for the procedure. The article claims that the routine use of enema before labour is not necessary. Every woman is an individual with different knowledge about enema. Not all pregnant women have problems for which therapeutic enema (i.e. to relieve constipation) would be indicated.
Keywords: childbirth; klistir; porod; priprava